Left site perforated appendicitis associated to midgut malrotation in a patient in the third decade of life: a case report - Hernandez-Licona, Jennifer; Martin Hernández, Jesus Antonio; Cutipa-Flores, Gainsborough Gonzalo (International Journal of Research in Medical Sciences, 2024)
Acute appendicitis represents the most common surgical emergency in the world. Clinically, it presents with pain in the right iliac fossa. One third of patients presents with pain in another location, secondary to the variability of the anatomical position of the appendix. Acute left appendix is a very rare pathology, and it is commonly associated with congenital anomalies such as intestinal malrotation or situs inversus. The patient in this case, a 30-year-old male, presented with abdominal pain in the epigastrium which later radiated to the hypogastrium. Initially with a diagnosis of suspected gastroenteritis, with no improvement with treatment, it was decided to perform an abdominal tomography, where the left cecal appendix was observed, with increased diameter, associated with signs of midgut malrotation. Diagnostic laparoscopy was performed, and no appendix was identified. It converted to open surgery, revealing small intestine on the right side, colon on the left side and perforated left cecal appendix. Acute left appendicitis it should be suspected early to avoid delay in diagnosis and treatment, and to avoid future complications. Abdominal tomography is a highly sensitive diagnostic tool in the case of acute appendicitis associated with intestinal malrotation. Laparoscopy is the first choice in suspected left appendicitis, but the surgeon must take into account the difficulties that may arise during the procedure, the time of evolution and not delay definitive treatment; it must also decide when open surgery is necessary.